DIATOM TEST AND DROWNING: RAPE AND MURDER CASE IN INDIA (Journal of Forensic Medicine & Toxicology, 2013)
In the country’s most high profile case “Shopian Rape and murder case” in which bodies of two female victims named ‘Asiya Jaan’ and ‘Neelofar Jaan’ were found in Rambiara water stream on 30thMay’2009 at Jammu and Kashmir. The investigations first declared it to be rape and murder. Later the case was sensitized in which the doctors opined that the hymen of deceased ‘Asiya Jaan’ was intact and the injury on the forehead was not enough to cause death. While another deceased ‘Neelofar Jaan’ was married on whom no antemortem injuries were found. The diatom test was conducted at Forensic Science Laboratory (Haryana) Madhuban which showed the presence of diatoms in the biological tissue samples of ‘Asiya Jaan’ and ‘Neelofar Jaan’ and in the water sample of the stream. After the diatom test medical doctors opined that death of two female victims was due to antemortem drowning.
Keywords: Diatom; Diatom Drowning; Forensic science; Shopian; Jammu and Kashmir